The Integration of Positive and Islamic Law in Contemporary Forest Conservation Policies Based on Sustainable Development: A Comparative Study of Indonesia and Malaysia - Absori; Arief Budiono; Mohammad Indra Bangsawan; Rizka; Aminuddin Mustaffa (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This study examines the integration of positive law and Islamic law within contemporary sustainable development–based forest management conservation policies through a comparative analysis of Indonesia and Malaysia. The research aims to analyze the normative and regulatory frameworks governing forest conservation in both countries and explore the extent to which Islamic legal principles are incorporated into state-based environmental governance. Employing a qualitative doctrinal and comparative legal approach, this study analyzes statutory regulations, policy documents, judicial decisions, and relevant Islamic legal sources, complemented by secondary scholarly literature. The analytical framework combines sustainable development theory with maqāṣid al-sharīʿah to assess how environmental protection aligns with both constitutional mandates and Islamic normative objectives. The findings reveal that Indonesia and Malaysia demonstrate different models of legal integration. Indonesia tends to institutionalize environmental protection through constitutional and statutory mechanisms, while incorporating Islamic values in a more implicit, socio-cultural manner. In contrast, Malaysia exhibits a more formal recognition of Islamic legal principles within state-level religious and environmental governance structures. Despite these differences, both countries reflect a converging commitment to ecological sustainability grounded in legal pluralism. However, challenges remain in harmonizing regulatory enforcement, addressing the drivers of deforestation, and ensuring community-based participation. This study contributes to the development of contemporary Islamic environmental jurisprudence by offering a comparative legal model of integrative governance between positive and Islamic law in forest conservation policy. It advances scholarly discourse on legal pluralism, sustainable development, and the operationalization of maqāṣid al-sharīʿah within modern environmental regulatory frameworks in Muslim-majority countries.